2009
DOI: 10.1016/j.cellsig.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Ras-PI3K interaction in the endosome using BiFC

Abstract: 3/21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 43 publications
(29 reference statements)
2
27
0
Order By: Relevance
“…We noted that mutagenesis of the residues in a stretch of amino acids in the switch I region (Figure 1A) ( i.e. , I36 - S39), or of the interacting residues on the primary effector proteins (RAF, PI3K or RALGDS), has been reported to lower binding affinity for effector proteins to RAS proteins (Colicelli, 2004; Gysin et al, 2011; Hall et al, 2002; Huang et al, 1998; Huang et al, 1997; Karnoub and Weinberg, 2008; Malumbres and Barbacid, 2003; Pacold et al, 2000; Scheffzek et al, 1997; Shaw and Cantley, 2006; Tanaka and Rabbitts, 2010; Tsutsumi et al, 2009; Vigil et al, 2010; Walker and Olson, 2005). Analysis of the KRAS G12D (PDB: 4DSN, and see Supporting Information) structure revealed a candidate site in the switch I region (termed here the D38 site), and two additional potential binding sites near the D38 site (Figure 1B and Supporting Information): we identified a site centered on alanine 59 (termed the A59 site), located between the switch I and switch II regions; on the other side of the D38 site, we identified a potential binding site near Y32 (Figure 1B and Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We noted that mutagenesis of the residues in a stretch of amino acids in the switch I region (Figure 1A) ( i.e. , I36 - S39), or of the interacting residues on the primary effector proteins (RAF, PI3K or RALGDS), has been reported to lower binding affinity for effector proteins to RAS proteins (Colicelli, 2004; Gysin et al, 2011; Hall et al, 2002; Huang et al, 1998; Huang et al, 1997; Karnoub and Weinberg, 2008; Malumbres and Barbacid, 2003; Pacold et al, 2000; Scheffzek et al, 1997; Shaw and Cantley, 2006; Tanaka and Rabbitts, 2010; Tsutsumi et al, 2009; Vigil et al, 2010; Walker and Olson, 2005). Analysis of the KRAS G12D (PDB: 4DSN, and see Supporting Information) structure revealed a candidate site in the switch I region (termed here the D38 site), and two additional potential binding sites near the D38 site (Figure 1B and Supporting Information): we identified a site centered on alanine 59 (termed the A59 site), located between the switch I and switch II regions; on the other side of the D38 site, we identified a potential binding site near Y32 (Figure 1B and Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…One interpretation of this is that, besides Cdc42, there may be additional endomembrane effectors that need to be activated for more efficient transformation. Intriguingly, Tsutsumi et al have recently examined the binding between H-Ras and the catalytic subunit of PI3K and found that this also occurs in endosomes (48). It is possible that some fractions of PI3K may be activated by Ras in the endomembrane but not the PM, as generally assumed, during transformation.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that Spred-2 also regulates the PI3K signaling pathway, as the Raf-MEK-ERK and PI3K signaling pathways functionally cross-regulate each other (43, 44). Several studies also report that PI3K signaling regulates influenza virus entry (4547). Our findings indicated that Spred-2 deletion enhanced the phosphorylation status of Akt, a commonly used marker of PI3K activation.…”
Section: Discussionmentioning
confidence: 99%